Deciphering the Voynich manuscript: propositions to unlock research. Issue 5 (3rd September 2022) - Parmentier, François
Abstract : The Voynich Manuscript is a medieval book, whose text has continuously resisted decoding efforts for more than a century. First, propositions are made to insure a good overall quality of research about this manuscript. Next, two common assumptions, correspondingly about the manuscript writing system and the presence of labels, are questioned. As a result, a certain number of irregular forms of letters are pointed out and tentatively explained; and labels are found to be sometimes widespread words or refer to different objects (plants, stars…). Theoretical implications of such empirical findings are discussed, and call into question the validity of natural language hypothesis.